Pengaruh Bonus Plan dan Corporate Governance pada Income Smoothing - Dwiadnyani, Ni Made; Mertha, I Made (E-Jurnal Akuntansi, 2018)
GCG mechanism as a supervisory company is considered able to protect investors and trust will get the return of the investment made. This study aims to obtain empirical evidence on the effect of Bonus Plan and Corporate Governance on Income Smoothing. The study was conducted on companies listed on the Indonesia Stock Exchange and entered into Corporate Governance Perception Index (CGPI) rankings respectively, and companies that did not suffer losses for the period 2011-2016. The sample is determined by purposive sampling method. The sample obtained by 7 companies with observation for 6 years so that got the amount of sample as much as 42 observation. The analysis technique used is Logistic Regression Analysis. Based on the analysis results found that the bonus plan has no positive effect on income smoothing. While corporate governance has no negative effect on income smoothing. This shows the high motivation Bonus Plan and the implementation of Corporate Governance does not necessarily affect the possibility of Income Smoothing. Keywords : income smoothing, bonus plan, corporate governance